Body movements on the men's competition mushroom: a three dimensional analysis of circular swings. Issue 8 (25th July 2005) - Grassi, G; Turci, M; Shirai, Y F; Lovecchio, N; Sforza, C; Ferrario, V F
Abstract : Objectives: To develop a method for the three dimensional analysis of body movements and body positions during the performance of circular swings on the competition mushroom, an apparatus used by young gymnasts for pommel horse training. Methods: Five experienced male gymnasts, all of national level, performed three series of 10 circular swings on the competition mushroom. An optoelectronic instrument was used for the detection of the three dimensional movement of 13 body landmarks. From landmark trajectories, several technical measurements were obtained: diameters of ideal circles of ankles, hips, shoulders; deviation of the ankle diameters from circularity and from the horizontal plane; angle between the shoulder, hip, and ankle. The values were used for a quantitative assessment of performance of the five gymnasts. Results: During the exercise, each ankle should follow a nearly horizontal circular path (deviation from circularity ranged from 3.6% to 6%, deviation from horizontality was 9.4–19.7%), there should be an angle of about 180° at the hips (actual values 146–153°), and the shoulders should move as little as possible, and only in the lateral plane, without major anteroposterior movements (shoulder movement was 27–31% of ankle movement, hip movement was 16–20%). Conclusions: The method could help coaches and gymnasts to determine which parts of the body are not repeating a selected movement with sufficient accuracy and to quantify improvements made after a specific training programme.